Versican/PG-M assembles hyaluronan into extracellular matrix and inhibits CD44-mediated signaling toward premature senescence in embryonic fibroblasts - Keittisak Suwan (2018)
Versican/PG-M is a large chondroitin sulfate proteoglycan of the extracellular matrix which interacts with hyaluronan at the N-terminal G1 domain, composed of A, B, and B′ subdomains. Recently, we generated knock-in mice Cspg23/3, whose versican, without the A subdomain, has decreased hyaluronan (HA) binding affinity, thereby exhibiting reduced deposition of versican in the extracellular matrix. Here, we show that the Cspg23/3 fibroblasts within 20 passages proliferate more slowly and acquire senescence. Whereas the extracellular matrix of the wild type fibroblasts exhibited a network structure of hyaluronan and versican, that of the Cspg23/3 fibroblasts exhibited ∼35 and ∼85% deposition of versican and HA, without such a structure. The Cspg23/3 fibroblasts showed a substantial increase of ERK1/2 phosphorylation and expression of senescence markers p53, p21, and p16. Treatment of wild type fibroblasts with hyaluronidase and exogenous hyaluronan enhanced ERK1/2 phosphorylation, and treatment with an anti-CD44 antibody that blocks HA-CD44 interaction inhibited the phosphorylation. These results demonstrate that versican is essential for matrix assembly involving hyaluronan and that diminished versican deposition increases free hyaluronan fragments that interact with CD44 and increase phosphorylation of ERK1/2, leading to cellular senescence. © 2009 by The American Society for Biochemistry and Molecular Biology, Inc.